Field Evaluation of the Stability of a Mountainous Road in theKurdistan Region of Iraq - Hamawandy, Mohammed J.; Sissakian, Varoujan K.; Hassan, Shatha F.; Ghafour, Bahra Dh. (Iraqi Journal of Science, 2025)
The majority of the roads in the Kurdistan Region of Iraq (KRI) are mountainous, with steep ascending and descending slopes and acute curves. Therefore, the road cuts on both sides of the roads usually suffer from slope stability problems exhibiting different types of slope failures. One of the easiest methods to assess the stability of road cuts is the Bejerman Method. It is a field method based on 10 different attributes, which can be measured and/ or estimated directly in the field. The studied area is located in the High Folded Zone, which is a part of the Unstable Shelf and occupies the northeastern part of the Arabian Plate, and is characterized by different types of mass movements; like landslides and toppling, as well as active weathering and erosion, and highly weathered rocks. The Bejerman Method was applied on a selected segment of the road that crosses Haibat Sultan Mountain near Galka Smaq village in KRI. The studied part of the road was covered by 13 stations, and at each station, we measured and/ or estimated the 10 attributes at each station. The results showed that among the 13 studied stations, the Landslide Possibility Index )L.P.I.( ranking showed 4 scored Very High, 5 scored High, 3 scored Medium, and 1 scored Low. It’s recommended to construct side and top ditches to reduce the water infiltration, decrease the slope gradients at the road cuts, and increase the vegetation cover on slopes.